Pengembangan Sistem Informasi Berbasis Web di BMKG Stasiun Geofisika Kelas III Malang: Studi pada Modul Data Hilal - hidayatullah, lailatul fadhilla nur (Maliki Interdisciplinary Journal, 2025)
This research aims to develop a web-based information system at the BMKG Class III Malang Geophysical Station to facilitate the management and presentation of observation data, especially crescent moon observations. This system is built using the CodeIgniter 4 framework with a Model-View-Controller (MVC) architecture, and utilizes PHP, HTML, CSS (Bootstrap), JavaScript, and MySQL. Key features include daily statistics and news displays for general users, as well as an admin dashboard for observation data management through CRUD features and Excel file uploads. The development process includes data collection, system design, implementation, and testing. Test results show that the system runs stably and functionally, and receives positive feedback from internal users. This system is expected to improve the efficiency, transparency, and accessibility of geophysical and astronomical observation information within the BMKG environment.